The effects of combined co-expression of groel/es and trigger factor chaperone towards Thermus thermophilus DNA polymerase enzyme expression on Escherichia coli BL21(DE3) - Iman Permana Maksum, Diandra Firdiani Utami, Sriwidodo Sriwidodo, Ryan Adibagus Haryanto, Riyona Desvy Pratiwi (Journal of Applied Pharmaceutical Science, 2024)
The Thermus thermophilus (Tth) DNA polymerase enzyme, originating from the thermophilic bacterium T. thermophilus, exhibits bifunctionally as both a DNA polymerase and a reverse transcriptase. When expressed in Escherichia coli, the T. thermophilus DNA polymerase enzyme frequently results in the formation of inclusion bodies. This occurrence is attributed to the rapid rate of protein expression in E. coli which surpasses the availability of chaperone proteins and reduced cytoplasmic conditions. The formation of inclusion bodies can reduce the recovery of soluble protein. A combination of GroEL/ES and trigger factor chaperone co-expression was used to overcome this deficiency. Thermus thermophilus gene DNA Pol/pG-Tf3 was transformed into the host E. coli BL21(DE3) and expressed with and without chaperone co-expression. Utilizing co-expression of the chaperone combination GroEL/ ES and trigger factor can reduce the formation of inclusion bodies or decrease the insoluble fraction in the expression of the T. thermophilus DNA polymerase enzyme, resulting in a co-expression total protein content of 3.9258 mg/ml.
Keywords: Chaperone, E. coli, GroEL/ ES, T. thermophilus DNA polymerase, trigger factor